2022
DOI: 10.1177/11206721221077621
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in CYP1B1 gene and the risk of suffering Primary Open-Angle Glaucoma: Systematic review and meta-analysis

Abstract: Purpose It had been reported that mutations in CYP1B1 gene probably play an important role in the pathogenesis of primary open angle glaucoma (POAG) but the existing genetic association studies show contradictory results. Thus, the objective of our study was to perform a systematic review and meta-analysis to characterize more precisely the potential association between given polymorphisms in CYP1B1 gene and the risk of suffering POAG. Methods A systematic review of studies that related the risk of carrying CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A previous study shows that L432V generates oxidative stress resulting from higher reactive oxygen species in retinal pigment epithelial cells and might lead to apoptotic changes causing retinal ganglion cell loss and glaucoma in an animal model 39 . Also, several studies have shown that CYP1B1 L432V is associated with glaucoma 22,39–43 . In this study, polymorphisms CYP1B1 L432V and MYOC R76K are associated with POAG suspects, which warrants additional data to explore their combined role.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A previous study shows that L432V generates oxidative stress resulting from higher reactive oxygen species in retinal pigment epithelial cells and might lead to apoptotic changes causing retinal ganglion cell loss and glaucoma in an animal model 39 . Also, several studies have shown that CYP1B1 L432V is associated with glaucoma 22,39–43 . In this study, polymorphisms CYP1B1 L432V and MYOC R76K are associated with POAG suspects, which warrants additional data to explore their combined role.…”
Section: Discussionmentioning
confidence: 62%
“…39 Also, several studies have shown that CYP1B1 L432V is associated with glaucoma. 22,[39][40][41][42][43] In this study, polymorphisms CYP1B1 L432V and MYOC R76K are associated with POAG suspects, which warrants additional data to explore their combined role.…”
Section: Discussionmentioning
confidence: 99%
“…[ 105 ] The prevalence rate of pathogenic variation in the CYP1B1 gene was higher in JOAG as compared to POAG. [ 106 ]…”
Section: Cytochrome P450 Family 1 Subfamily B Polypeptide 1 Gene (Cyp...mentioning
confidence: 99%